Analisis Yuridis Persekongkolan Tender Rehabilitasi Jalan dalam Perspektif Hukum Persaingan Usaha (Studi Kasus Putusan Nomor 14/Kppu.1/2018) - Abdul Hafiz Rangkuti; Taufik Siregar; Zaini Munawir (Universitas Medan Area, 2022)
In general, what is said to be conspiring is cooperation carried out by business actors with other parties at the initiative of anyone and in any way in an effort to win bidders. The purpose of the research is to find out and understand how the regulation regarding tender conspiracy according to business competition law in Indonesia, to know and understand the proof of tender conspiracy as well as to know and understand how the application of business competition law in decision Number 14/KPPU.I/2018. The method used in this paper is normative juridical, namely a research method that examines document studies, by using various data such as legislation, legal theory of court decisions.The result of the research written in this thesis is that the regulation regarding tender conspiracy is regulated in Article 22 of Law no. 5 of 1999 and regulated in Perkom No. 1 of 2019, evidence regarding tender conspiracy in decision number 14/KPPU.1/2018 is an element of conspiracy in article 22 of Law no. 5 of 1999 is fulfilled and based on the evidence in Article 45 of Perkom No.1 of 2019 is fulfilled, the application of business competition law in decision number 14/KPPU.1/2018 is to provide administrative action in the form of a fine to punish the Reported Party I and II in the amount of Rp.1,769,000. 000, which must be deposited into the State Treasury. The conclusion of the arrangement regarding tender conspiracy is regulated in Article 22 of Law No. 5 of 1999 and regulated in Perkom No. 1 of 2019. The evidence regarding tender conspiracy in decision number 14/KPPU.1/2018 is an element of conspiracy in article 22 of Law no. 5 of 1999 is fulfilled, the application of business competition law in decision number 14/KPPU.1/2018 provides administrative action in the form of a fine.